Analysis of qualitative data from the investigation study in pregnancy of the ASSIST Version 3.0 (the Alcohol, Smoking and Substance Involvement Screening Test). (March 2016) - Hotham, Elizabeth D.; Ali, Robert L.; White, Jason M.
Abstract: Objective: to utilise qualitative data from investigation of the screening tool ASSIST Version 3.0 with pregnant women to help determine its appropriateness for this cohort, thus informing potential innovations to enhance the questionnaire׳s utility. Design: pregnant women were co-administered the ASSIST Version 3.0 and three established substance use questionnaires (the T-ACE for alcohol, the Timeline FollowBack for cannabis and the Revised Fagerstrom Questionnaire for tobacco). Setting: antenatal clinics and the antenatal ward of the Women׳s and Children׳s Hospital, Adelaide, South Australia. Participants: 104 pregnant substance-users. Measurements and findings: as well as the quantitative date (reported elsewhere), rich qualitative data documenting participants' perspectives and experiences in antenatal care were thematically analysed. Women constantly reported friends and family urging them to stop use. Although care providers also advocated cessation or curtailment of use, this advice was reported as unpredictable, with only some providers strongly attuned to such recommendations. Some women voiced suggestions for the appropriate level of provider advice. While pregnancy was often reported as a motivator for changing substance-using behaviour, others reported continued attachment to use which was clearly linked to dependence. Those who reported successful control of use were in contrast to others who were more pragmatic, sceptical in relation to attributable harms, and disinterested in change. There were limited reports of experiences of discrimination directed to pregnant substance users. However, those instances were clearly linked with subsequent lack of honest discussions with care providers, resulting in an absence of appropriate support. Key conclusions: current absence of universal screening for substance use has the potential for less than optimal consequences for both mother and baby. Implications for practice: appropriate screening accompanied by honest, non-judgmental dialogue can guide the necessary interventions to achieve better outcomes. The recent development of the more concise and easier to administer ASSIST-LITE was partly informed by this investigation.